Brewer's dictionary of phrase and fable - Brewer, Ebenezer Cobham (Harper & Row, 1965)
Since its first publication in 1870, Brewer's Dictionary of Phrase and Fable has become one of the world's best-loved and most-browsed-through books. Where else can one find the meanings of - and the stories behind - so many terms and phrases drawn from mythology, literature, history, folk customs, pop culture, philosophy, science, magic, and superstitions? From expressions as common as sour grapes to allusions such as Pyrrhic victory, Dr. Brewer and his editorial successors both teach and delight the reader, offering unusual, out-of-the-way, and fascinating information on thousands of familiar - and unfamiliar - phrases. Completely revised, updated, and expanded, this fifteenth edition contains hundreds of new entries, improved etymologies, and a reorganized format that make Brewer's Dictionary of Phrase and Fable even more of a delight than ever.